Analysis of Income Differences Between Rural and Urban Areas in Serbia - Dejan Brcanov (Anali Ekonomskog fakulteta u Subotici, 2025)
This study explores income disparities within the rural-urban divide through a multidisciplinary approach, incorporating factors such as education, gender, employment, and household size, with the aim of providing insights for the development of effective policies and promoting inclusive regional development.Data were collected from the SILC database conducted in Serbia in 2022. A univariate analysis was performed with all control variables, and subsequently a multiple regression analysis. The inclusion of control variables further illuminates the income differences observed between rural and urban areas. Our findings confirm that income levels are higher in urban areas compared to rural ones. The influence of other variables is consistent with the literature.Future research will adopt a longitudinal approach and include additional socio-economic indicators, which could offer further explanations for income disparities between urban and rural regions.